Prevalence and professional implication of updated versus previous hypertension classification - Nsanzabera, Charles; Sagwe, Daniel Nyamongo; Ndengo, Marcel (International Journal Of Community Medicine And Public Health, 2020)
Background: Hypertension remains the global challenge and the leading causes of worse cardiovascular event with 7.5 million toll deaths. The 2010 WHO estimate was 1.3 billion representing 31.1% of all adults with an astounding increase in low and middle-income countries including Sab-Saharan Africa. Methods: This cross-sectional study was undertaken in two beverage industrial workplaces with a sample of 440 employees and their spouses during the period of 2016 to 2018. WHO stepwise questionnaire was used to collect data and biomedical samples were taken for predicting the 10-year cardiovascular risk by Cox regression model and multivariate logistic regression was run to determine the key factors associated with both Hypertension (HTN) classifiers. The data were coded and analyzed by SPSS 16.0 version. Results: Overall HTN prevalence was 32.27%, male with 37.8% and female with 25.2% by previous HTN classifier. Whereas the updated classifier showed an overall prevalence of 61.81%, male with 67.1% and female with 55%. The findings showed a huge difference of 29.54% with p<0.001 between the two prevalence of previous and updated blood pressure classification. Employees had a relatively high HTN prevalence of 35.92% to 65.18%, compared to the spouses with 26.47% to 56.47%, p<0.001 by previous and updated classification, respectively. Conclusions: The relatively rise prevalence of the HTN revealed by this study suggests new and combining health promotion tactics, cultural theories to fight this rampant silent killer.